Ragweed pollen rain impact on allergy rate and severity in Krasnodar: a three-year non-randomised controlled study - Ya. V. Klimenko; N. O. Milchenko; A. N. Moroz; I. I. Pavlyuchenko; E. A. Alekseenko (Кубанский научный медицинский вестник)
Background. The main hay fever agent in Krasnodar Krai is ragweed pollen (Ambrosia gen.). An important alerting guide for medical practitioners and allergic citizens is the seasonal anthetic calendar and pollen peak times.Objectives. Obtaining of relevant data on ragweed pollen air contamination rate in Krasnodar in a three-year-dynamics (2018–2020) to estimate the anthetic activity correlation with abiotic and anthropogenic factors and the role of pollen indicators in allergic morbidity.Methods. We surveyed the daily average ragweed pollen values in Krasnodar air. Allergic medical visits were analysed in terms of the ragweed anthetic activity and pollen air contamination of the city.Results. A maximal daily average ragweed pollen peak occurs in August: 663.35 p.g./m3 in 2018, 209.89 p.g./m3 in 2019, 80.62 p.g./m3 in 2020. Numbers of medical visits for pollinosis per a selected municipal medical facility: 314 in 2018, 335 in 2019 and 146 in 2020, with a peak period in September--October. Analyses of the air pollution impact on ragweed pollen production revealed a correlation between the pollen rate and values of CO (correlation coefficient r-0.356), NH3 (r-0.198) and dust pollution (r-0.361) in July, August, September and October 2018–2020.Conclusion. Analyses of climatic factors uncovered clear patterns: strongest anthesis corresponds to minimal humidity (<60%), the pollen grain content diminishes with lower humidities dropping to minimal with precipitations and increases at temperatures 20 °C and above. No significant dependency was observed between air pollution and the allergic pollen content. Anthesis in ragweed moderately correlates with the rate of medical visits.